2020
DOI: 10.1002/ece3.6757
|View full text |Cite
|
Sign up to set email alerts
|

Macrosystems EDDIE teaching modules significantly increase ecology students' proficiency and confidence working with ecosystem models and use of systems thinking

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 53 publications
1
23
0
Order By: Relevance
“…For example, instructors of introductory courses may choose to teach module activities A and B in a class and then assign activity C as homework or omit certain activities, while instructors of more advanced courses may choose to assign activity A for pre-class homework and complete activities B and C in class. Modeling activities and associated worksheets and handouts follow the 5Es of learning (engagement, exploration, explanation, expansion, and evaluation) [35,42] and are designed to foster hypothesis-driven exploration of ecosystem model outputs following [43]. Modules generally increased in complexity from Module 1 to Module 4, though none of the modules have pre-requisites and modules can be used in any order as stand-alone activities.…”
Section: Macrosystems Eddie Modulesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, instructors of introductory courses may choose to teach module activities A and B in a class and then assign activity C as homework or omit certain activities, while instructors of more advanced courses may choose to assign activity A for pre-class homework and complete activities B and C in class. Modeling activities and associated worksheets and handouts follow the 5Es of learning (engagement, exploration, explanation, expansion, and evaluation) [35,42] and are designed to foster hypothesis-driven exploration of ecosystem model outputs following [43]. Modules generally increased in complexity from Module 1 to Module 4, though none of the modules have pre-requisites and modules can be used in any order as stand-alone activities.…”
Section: Macrosystems Eddie Modulesmentioning
confidence: 99%
“…To address this gap in ecology and biology training, we developed four stand-alone teaching modules as part of the Macrosystems EDDIE (Environmental Data-Driven Inquiry and Exploration) program (Table 1) that can be readily adapted and implemented by instructors. Each module addresses a key concept in macrosystems ecology (i.e., cross-scale interactions, teleconnections, or macro-scale feedbacks) through the lens of freshwater ecology and uses high-frequency and long-term data from NEON and/or GLEON lakes to run ecosystem simulation models in the R software environment [35,36]. Each module simultaneously teaches the core concepts of macrosystems ecology, and the quantitative and computational skills needed to conduct cutting-edge ecological research and can be easily implemented in a wide range of ecology and biology classrooms that otherwise might not cover concepts in macrosystems ecology as part of their curricula.…”
Section: Introductionmentioning
confidence: 99%
“…The challenge of addressing all the embedded concepts within ecological forecasting (e.g., mathematics, statistics, data science, social science, ecological modeling, science communication) may explain why it has not yet been broadly adopted in undergraduate classrooms, in addition to the field's recent development. Moreover, because the practice of ecological forecasting requires programming and modeling, skills rarely taught to undergraduates [20], the intimidation barrier to both teaching and learning forecasting may be high. New approaches are needed to integrate ecological forecasting into undergraduate classrooms to overcome these barriers of teaching INTEF at an appropriate introductory level.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the use of open data for data-driven inquiry has been a common theme for "emergency" virtual ecological instruction during the pandemic (Acevedo 2020; Thompson et al 2020), and participants of the MSB-NES meeting indicated that NEON datasets were instrumental in making the change to remote classrooms. For instance, participants at the MSB-NES meeting who teach in higher education used NEON data for quantitative exercises in place of data that students would have otherwise collected in the field during class (eg the Macrosystems Environmental Data-Driven Inquiry and Exploration [EDDIE] modules for modeling ecosystem simulations at NEON sites [Carey et al 2020]). Likewise, the NEON-EREN (Ecological Research as Education Network) collaboration produced flexible learning projects in which ~700 students collected their own local datasets (that is, from campuses, parks, and backyards) to compare with NEON's continental-scale datasets.…”
mentioning
confidence: 99%
“…For instance, participants at the MSB–NES meeting who teach in higher education used NEON data for quantitative exercises in place of data that students would have otherwise collected in the field during class (eg the Macrosystems Environmental Data‐Driven Inquiry and Exploration [EDDIE] modules for modeling ecosystem simulations at NEON sites [Carey et al . 2020 ]). Likewise, the NEON–EREN (Ecological Research as Education Network) collaboration produced flexible learning projects in which ~700 students collected their own local datasets (that is, from campuses, parks, and backyards) to compare with NEON’s continental‐scale datasets.…”
mentioning
confidence: 99%